Peridynamics boundary condition treatments via the pseudo-layer enrichment method and variable horizon approach. (May 2021) - Chen, Jingkai; Jiao, Yiyu; Jiang, Wenchun; Zhang, Yanting
Peridynamics is a nonlocal theory that applies an integral term to represent the material response. Without a spatial differential term involved, peridynamics possesses certain advantages for solving discontinuity-involved problems. However, due to the reduction of stiffness, the deformation near the boundary region by peridynamics has a low accuracy compared to the local elastic deformation. Previous peridynamics boundary condition treatment enriches the stiffness on the boundary region by adding an artificial layer outside the domain boundary. However, this requires the deformation of the pseudo-layer to be pre-determined. In addition, the accuracy of the response on the physical domain depends largely on the accuracy of the pre-determined deformation on the pseudo-layer. Considering the fact that peridynamics reduces to local elasticity as the horizon size goes to zero, and previous researches indicate the potential advantage of boundary enrichment via the horizon varying approach, in this paper, peridynamics with a variable horizon is utilized as an efficient way to reduce the boundary-induced inaccuracy. Firstly, the pseudo-layer boundary condition treatments are discussed by using the symmetrical enrichment function and other extrapolation functions. Then, the variable horizon boundary condition treatment is introduced and a robust improvement of deformation accuracy on the boundary region is observed compared to other boundary condition treatments for both one- and two-dimensional examples. The variable horizon approach requires no additional pseudo-layer and the boundary conditions are applied directly on the physical boundary. Thus, the variable horizon approach is easy to implement and its computational cost is reduced.